2022
DOI: 10.3389/fpubh.2022.981339
|View full text |Cite
|
Sign up to set email alerts
|

Circulating (1 → 3)-β-D-Glucan as an immune activation marker decreased after ART in people living with HIV

Abstract: BackgroundPlasma level of polysaccharide (1 → 3)-β-D-Glucan (βDG), as a diagnostic marker of invasive fungal infection has been reported to be elevated in people living with HIV (PLWH). We assessed the association of circulating βDG to inflammation and systemic immune activation and the effect of antiretroviral therapy (ART) on βDG in PLWH.MethodPlasma and peripheral blood monocular cell samples from 120 PLWH naive to ART and after 1 year's ART were collected. Plasma levels of βDG, markers of bacterial translo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Similar findings were obtained in a very recent study where BDG levels in HIV patients decreased after 1 year of anti-retroviral therapy. 36 The absence of correlation with other permeability markers might also be partially explained by another mechanism acting a part, which is a decrease in BDG clearance by the hepatic reticuloendothelial system with increasing hepatic inflammation and hence higher levels in peripheral blood. 32 In a mouse model, Yang et al observed that a decrease in intestinal fungal overgrowth by non-absorbable Amphotericin B did not alter the gut barrier function and permeability remained increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were obtained in a very recent study where BDG levels in HIV patients decreased after 1 year of anti-retroviral therapy. 36 The absence of correlation with other permeability markers might also be partially explained by another mechanism acting a part, which is a decrease in BDG clearance by the hepatic reticuloendothelial system with increasing hepatic inflammation and hence higher levels in peripheral blood. 32 In a mouse model, Yang et al observed that a decrease in intestinal fungal overgrowth by non-absorbable Amphotericin B did not alter the gut barrier function and permeability remained increased.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were obtained in a very recent study where BDG levels in HIV patients decreased after 1 year of anti‐retroviral therapy. 36 The absence of correlation with other permeability markers might also be partially explained by another mechanism acting a part, which is a decrease in BDG clearance by the hepatic reticuloendothelial system with increasing hepatic inflammation and hence higher levels in peripheral blood. 32…”
Section: Discussionmentioning
confidence: 99%